Good outcome of newborn septic arthritis with holistic treatment: a case report - Muhammad Irvan Avandi; Brigitta Ida Resita Vebrianti Corebima; Eko Sulistijono; Talita Clarissa Sinatra (Pediatric Sciences Journal, 2022)
Introduction: Septic arthritis (SA) is a serious joint infection associated with significant morbidity that can cause permanent damage with articular cartilage destruction, osteonecrosis, and lifelong deformities. Here we present a good outcome of newborn septic arthritis with prompt treatment. Case Presentation: A one-month-old boy was brought with swelling of both knee joints two weeks before admission. He has a history of preterm birth and was hospitalized in the Neonatal Intensive Care Unit (NICU) because of neonatal pneumonia and sepsis. Several days after treatment, he came with swollen on both knees, both knee joint synovial liquid and sputum culture showed Klebsiella pneumoniae. Magnetic Resonance Imaging (MRI) was found intra articular fluid and erosion of the epiphyseal cartilage suspect infection process. After establishing the diagnosis of SA, we initiated treatment with cloxacillin 60 mg/kgs body weight for 14 days. He underwent debridement and physiotherapist. One year after discharge, the physical examinations showed normal findings and had a normal gait. Conclusion: It can be concluded that prompt diagnosis and treatment of SA on the newborn will have a good outcome with no sequelae. An early diagnosis of SA can guide clinicians to initiate a standardized treatment and improve patient outcomes.